Miniature Lamp House Media Innovation Solutions for Elementary School Students' Understanding: Inovasi Media Miniatur Rumah Lampu Solusi Pemahaman Siswa Sekolah Dasar - Ana, Miko Fitri; Zaitun, Iin; Barizi, Ach.; Yayuk, Erna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Teaching Natural Sciences (IPA) in elementary school often encounters challenges due to the abstract nature of certain concepts, such as electrical energy. Specific Background: Traditional instructional approaches may fail to engage students or provide concrete experiences needed for deep understanding. Knowledge Gap: There is limited research on the effectiveness of hands-on, contextual media in enhancing conceptual comprehension in electricity among elementary students. Aims: This study investigates the effectiveness of a miniature lamp house as an instructional medium to improve students’ understanding of electric circuits and energy flow. Results: Using a descriptive qualitative method with 16 fifth-grade students at SD Muhammadiyah 29 Surabaya, data collected through observation, interviews, and documentation—analyzed via the Miles and Huberman model—showed increased student engagement, enhanced conceptual understanding of electricity, and improved learning outcomes. Novelty: The miniature lamp house not only made abstract content tangible but also fostered collaboration and exploration, offering an innovative, low-cost learning tool aligned with the Merdeka Curriculum. Implications: The findings support the integration of concrete, student-centered media to strengthen basic science literacy and contribute toward achieving SDG 4: Quality Education, especially in promoting inclusive and equitable learning at the elementary level. Highlights: Enhances understanding of abstract science concepts. Promotes active learning and collaboration. Supports SDG 4 through inclusive, contextual education. Keywords: Miniature Lamp House, Instructional Media, Elementary Science, Conceptual Understanding, Merdeka Curriculum